(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the antiparasitic potential and cytotoxic effect of extracts by the leaves and roots of S. tuberosa. The results show that the extracts of S. tuberosa have low antipromastigote activity against strains of L. braziliensis, since there was no action at concentrations ≤ 500 µg/mL. While for L. infantum there was a significant action of the hydroalcoholic extract of the roots against promastigote forms, since there was 29.33 ± 1.94% of mortality for the treatment of 1000 µg/mL. The same extract showed antiepimastigote action against T. cruzi at a concentration ≥ 1000 µg/mL. Despite the low antiparasitic activities, it is possible to observe that the extracts of S. tuberosa have no cytotoxic action, except the hydroalcoholic extract of the roots. In this extract there was a total of 27.85 ± 2.41% of cytotoxicity against fibroblastic cells, in the highest concentration evaluated (1000 µg/mL).